2018
DOI: 10.1016/j.pedneo.2017.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus associated hospitalizations in children with congenital diaphragmatic hernia

Abstract: We found a moderate rate of proven RSV hospitalizations in infants with CDH, and palivizumab prophylaxis led to a non-significant reduction of proven and hypothesized RSV hospitalizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 17 publications
0
20
0
2
Order By: Relevance
“…Since the affected lung will be compressed by internal organs which occupy space during intrauterine development of CDH children, its development will be impaired to varying degrees; further, since the healthy lung is affected by mediastinal movement, its respiratory function will also be impaired to some extent [19, 20]. Previously publications have reported that pulmonary dysplasia on the affected side mainly manifests in different degrees of alveolar surface area reduction, the reduced number of bronchial trees, the decrease in pulmonary vascular inner diameter, and thickening of the median membrane, all of which result in pulmonary hypertension [21, 22].…”
Section: Discussionmentioning
confidence: 99%
“…Since the affected lung will be compressed by internal organs which occupy space during intrauterine development of CDH children, its development will be impaired to varying degrees; further, since the healthy lung is affected by mediastinal movement, its respiratory function will also be impaired to some extent [19, 20]. Previously publications have reported that pulmonary dysplasia on the affected side mainly manifests in different degrees of alveolar surface area reduction, the reduced number of bronchial trees, the decrease in pulmonary vascular inner diameter, and thickening of the median membrane, all of which result in pulmonary hypertension [21, 22].…”
Section: Discussionmentioning
confidence: 99%
“…2 The efficacy of palivizumab prophylaxis in other high-risk populations, such as those with pulmonary abnormality or neuromuscular disease, is of concern. Resch et al 1 have reported a trend of reduction in the number of RSV-associated hospitalizations in infants with CDH receiving palivizumab prophylaxis, although the reduction was not statistically significant. However, this study has reported about only two proven RSV infections.…”
mentioning
confidence: 98%
“…We read with great interest the article authored by Resch et al 1 [1] that reported a moderate risk of respiratory syncytial virus (RSV)-associated hospitalizations in infants with congenital diaphragmatic hernia (CDH) and that palivizumab prophylaxis resulted in a nonsignificant reduction in the number of RSV-associated hospitalizations. Although this is an important finding having clinical implications, this study has some limitations, and we would like to make some comments on this article.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, prophylaxis may be considered for children <2 years of age who are on home oxygen, have had a prolonged hospitalization for severe pulmonary disease, or are severely immunocompromised. While limited evidence suggests that palivizumab may be beneficial in reducing the severity of RSV illness and RSV-related hospitalization (RSVH) [14, 17], the impact of RSV prophylaxis in CDH in early infancy remains unclear. Therefore, the primary objective of this article was to determine the risk of respiratory illness–related hospitalization (RIH) and RSVH in infants with CDH who received RSV prophylaxis with palivizumab during the RSV season compared to infants prophylaxed for standard indications (SIs) and those who received prophylaxis but were considered not at increased risk (NR).…”
mentioning
confidence: 99%